Analisis Kebutuhan Fasilitas Pusat Pelayanan di Ibukota Kecamatan Pulau Tanakeke - Fathurrahman Burhanuddin; Nurhidayat M. (Universitas Muslim Indonesia, 2022)
Spatial planning with a small area or classified as a small island has limited area functions that can be planned or developed. Affordable service conditions between the island and the mainland encourage the island to act as a service center or the capital of a sub-district with a service area for a group of surrounding islands by considering the efficiency and effectiveness of services in the activity center system. One of the islands is Tanakeke Island, which has a new role as the center of sub-district scale activities. The purpose of this study is to examine and review the condition of the island's facilities as a center of activity. This study uses an approach and analysis with the method of observing the condition of facilities and infrastructure juxtaposed with the population of sub-district services, and using several analyzes, one of the analyzes that will be used is using network analysis with a service area scheme as the location of activity centers in the main island. The results of this study can be an illustration of the local government to increase in the number of facilities and infrastructure to support the role of Tanakeke Island as the sub-district administrative service center.